Stress Coping Styles among Nursing Students - Mehrnoosh Inanloo; Robabe Baha; Naiemeh Seyedfatemi; Agha Fatemeh Hosseini (Tehran University of Medical Sciences, 2012)
Background & Objective: Nursing students usually experience various types of stress. Lack of stress coping strategies result in more stress, incompatibility, manifestation of disorders, and mental health problems. This study carried out to assess the methods of coping with stress among nursing students. Methods & Materials: In this cross-sectional study, 358 male and female bachelor of nursing students studying at Tehran University of Medical Sciences during the first semester of 2011-2012 were selected. Data were collected using the Coping Inventory for Stressful Situation and a demographic questionnaire. The data was analyzed using descriptive and inferential statistics in the SPSS-14. Results: There were 66.2% female and 33.8% male students in the study. The age of the students ranged 17-29 years. Most of the students aged 20-22 years (45%), were single (90.8%), were habitants of Tehran (53.1%), had an average economic status (72.1%), and were employed (20.9%). Of all, 19.3% had experienced stressful events in the last three months. A small number of the students (4.7%) suffered from chronic diseases. The nursing students mostly used problem-oriented coping style (56%). The emotion-oriented method was used among 45.99% of the students and the avoidance-oriented style was used among 39.34% of the students. There were no statistically significant relationship between the coping styles and the demographic characteristics. Conclusion: The problem-oriented, emotion-oriented, and avoidance-oriented styles were the most frequent styles used by the students, respectively. The mental health, particularly among nursing students who deal with patients and have important role in the health system, is important and requires special attention. The stress coping styles should be inserted in the educational curriculum of the nursing schools.